THE PROBLEM OF THE RELATIONSHIP BETWEEN THEORETICAL AND EMPIRICAL THINKING (Pedagogy of Higher and Secondary Education, 2010)
The article reveals some aspects of theoretical and empirical thinking and the question of their correlation opens up.
Keywords: thinking; theoretical thinking; empiric thinking